Fast Time Response Full Absorption Faraday Cup and Its Application in the Measurement of Intensive Electron Beam Diodes - Pengfei Zhang; Dingguo Lai; Hailiang Yang; Jiang Sun; Wei Luo (Energies, 2023)
A magnetically insulated transmission line (MITL) is an inevitable choice for ultra-high power density energy transmissions. Its working process is complex, with an obvious influence on the working process of electron beam diodes and other load devices. The power coupling process of an electron beam diode driven by an MITL is a difficult problem in pulse power applications. No research is available on the electron beam characteristics of its anode. In this paper, a fast time response full absorption Faraday cup was developed. An intense electron beam measurement waveform showing the multi-stage characteristics was obtained through measurements using the Faraday cup absorber as the anode of the electron beam diode. The stage characteristics of the beam were in good agreement with the vacuum transmission, magnetic insulation formation, and multi-stage process of the stable magnetic insulation. The beam intensity corresponded with the conduction current of the cathode. It was obviously smaller than the current of the anode. The results reflected the influence of the different processes of the magnetic insulation on the transmission line on the beam waveforms in the diode area and provided a reference for the power transmission of the power device and the load system design.